Love Scams and Its Legal Protection for Victims (Law Research Review Quarterly, 2021)
The new phenomenon of cybercrime appears along with the development of technology and communication. The phenomenon of cybercrime is not only experienced by the global community but also in Indonesia. In the world of internet crime, which is basically carried out by means of communication by cybercrime actors through the internet media, the victim is more trusted by the victim than direct communication from people who are well known, the purpose of this paper is to find out how urgent the protection of victims of cases of fraud in love relationships via the internet is urgent. Victims of love scams, who are generally women, are easily deceived and when the perpetrator commits a crime through a message via the internet, the victim provides feedback to the perpetrator, communication is carried out by the perpetrator on an ongoing basis so that the victim believes and falls into lassitude and generally loses money up to a fairly large nominal rupiah.